Students’ long-term orientation role in e-learning success - Cidral, Wilmar (2020)
Cidral, W., Aparicio, M., & Oliveira, T. (2020). Students’ long-term orientation role in e-learning success: A Brazilian study. Heliyon, 6(12), 1-12. [e05735]. https://doi.org/10.1016/j.heliyon.2020.e05735